(untitled) (Progressive Agriculture, 2013)
Cryopreservation is one of the widely accepted and useful methods for preservation of gamete especially the spermatozoa. Experiments were conducted to develop the protocols for cryopreservation of sperm of Labeo rohita and to assess the effect of cryopreserved sperm on fertilization and hatching. Six extenders Alsevers solution, egg-yolk citrate, urea egg-yolk, Kurokura-2, Ma and Mb and five cryoprotectants ethanol, methanol, DMSO, DMA and glycerol were employed. Diluents were prepared by mixing the cryoprotectants at 10% concentration of the extenders (% v/v). Milt and diluents were mixed at a ratio of 1:9 for Alsevers solution and Kurokura-2; and 1:4 for urea egg-yolk, egg-yolk citrate, Ma and Mb. Egg-yolk citrate with 10% DMSO showed best performance producing 85 ± 1.6% post-thaw motility followed by 83±2% and 81±2.9% with Alsevers solution and urea egg-yolk respectively. Other extenders did not produce satisfactory results. Milt was diluted at six ratios (1:2, 1:4, 1:7, 1:9, 1:15 and 1:20) and 1:4 dilution showed the highest post-thaw motility for egg-yolk citrate and urea egg-yolk and 1:9 for Alsevers solution. Six cryoprotectant concentrations (5, 7, 10, 15, 20% and 30%) were investigated and 10% concentration produced the highest post-thaw motility. In breeding trials, sperm preserved with egg-yolk citrate plus DMSO as well as Alsevers solution plus DMSO fertilized eggs and produced hatchlings. The fertilization and hatching rates were 57 ± 7% and 46.5 ± 3.5% for egg-yolk citrate, and 33.5 ± 3.5% and 27±3% for Alsevers solution respectively. Fresh sperm yielded 76 ± 4% fertilization and 70.5 ± 5.5% hatching. The protocol developed through this study can be applied for long-term conservation of genetic materials of L. rohita and the cryopreserved sperm can be used in artificial breeding for generating new individuals. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16474 Progress. Agric. 22(1 & 2): 123-137, 2011